Impact of strengthening exercices on the shoulder joint - Charbonnier, C.; Kevelham, B.; Chague, S.; Lädermann, A.; Ziltener, J.-L.; Hoffmeyer, P.; Holzer, N. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
Strengthening of shoulder muscles in rehabilitation protocols and sport practice can be achieved by a wide range of different exercises. Very limited objective data is at disposal to emit recommendations for design of a training protocol that aims at minimizing subacromial impingement, stress on the articular cartilages or labrum and excessive tendon elongation of the rotator cuff. The purpose of this study was to evaluate the impact of shoulder rehabilitation exercises on the shoulder joint using motion capture and computer simulations of patient-specific anatomical joint structures.